(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
The article provides a comprehensive analysis of the spiritual foundations of Turkic literature, with particular attention to the influence of the Islamic worldview, including the Qur’an, Hadith, and Sufi teachings. The conceptual framework of the study is based on the notions of Nūr al-Muḥammad and Ḥaqīqat-i Muḥammadiyya. According to these concepts, the light of the Prophet Muhammad is regarded as the primordial spiritual essence that existed prior to the creation of the world and serves as the fundamental principle of all existence. The article examines the manifestations of these notions in Turkic literature and Sufi texts, as well as their religious-philosophical significance. The object of the study is the manuscript Mecmūʿa-i Resāʾil-i ʿAcībe, written in Chagatai in 1909. This mejmua is characterized as a multifaceted text encompassing religious, Sufi, and everyday content. The “Nūr-nāme” section of the manuscript addresses the creation of the light of the Prophet Muhammad, the origin of the world, the history of the prophets, and religious conceptions of the Day of Judgment and the afterlife. Additionally, the manuscript contains information on daily life, customs, and agriculture, including prayers dedicated to farming and animal husbandry. From a linguistic perspective, the article provides a detailed analysis of the manuscript’s morphological system. The peculiarities of plural, possessive, and case suffixes are examined in relation to the phonetic and morphological rules of the Chagatai language. In particular, the coexistence of the two genitive forms (+nıñ/+niñ and +nı/+ni) reflects diachronic changes in the historical development of the language. Moreover, the functions of the dative, locative, ablative, instrumental, and directive cases are described with concrete examples, highlighting their role in the Turkic written tradition. In conclusion, the article demonstrates that a comprehensive analysis of the manuscript Mecmūʿa-i Resāʾil-i ʿAcībe as a literary, historical, and linguistic source makes a significant contribution to the study of the Turkic Sufi tradition and the development of the Chagatai language in the early twentieth century.